Cultura avaliativa e representações sociais com novos significados para a universidade - Tavares, Adriana Fátima (2018)
He challenge of the present study is to understand the process of self-evaluation at the State University of the West of Paraná, Unioeste, Cascavel, in the perspective of the participation of the academic community, having as its axis the social representations of the institutional actors of the evaluation process, aiming at the construction and consolidation of effective evaluation culture. We seek answers to the following questions: Are there institutional policies that motivate the implantation / formation / strengthening of the culture of institutional evaluation? How is the issue addressed in the different institutional instances? Why is there low adherence, participation and involvement of the academic community in the evaluation process, its effects and uses in the development of Unioeste? What is the relation of these aspects to the representations for the formation / strengthening of the evaluation culture that is wanted from the institutional self-evaluation? What are the challenges, weaknesses and potentialities of the institution to overcome the legal assistance scenario and give new meaning to the process of self-evaluation and the university? The study was guided by the induction method and was constituted by field research, exploratory in nature and descriptive, subsidized by bibliographical and documentary research. In the data collection, a questionnaire (Appendix 2) was applied to be answered by the components of the sample, institutional actors involved in the elaboration, conduction and management of the evaluation process of the university, object of study. In the analysis of the collected material, it was based on the individual conception of the participant to extend their social representations built for the collective understanding, with the objectives of understanding how the evaluation process takes place under the legal guidelines of the National System of Evaluation of Higher Education, Sinaes, to identify the existence (or not) of academic policies and practices that favor the formation / strengthening of the evaluation culture and to know how this culture is represented in the institutional context. In the referential, as a way of overcoming the coercive character of legal mechanisms and go beyond the discussion of compliance with the legislation of the Law of Sinaes, in the sociological bias, foundations and theoretical support were sought to discuss and analyze the content of the discourse of the component subjects of the sample, recorded in response to the questions in the questionnaire. In the analysis of the social representations of the institutional actors involved, we identified the main challenges, fragilities and institutional potential that favor /hinder the understanding and collective construction of the evaluation culture and the contribution of this culture in the formation of new representations with new meanings for Unioeste. The results of the study may contribute to the construction of actions that allow the articulation of management and optimization of planning and improvement of institutional quality, in order to effectively promote the construction / consolidation of the evaluation culture.